Initial cell maturity changes following transplantation in a hyaluronan-based hydrogel and impacts therapeutic success in the stroke-injured rodent brain. (February 2019) - Payne, Samantha L.; Tuladhar, Anup; Obermeyer, Jaclyn M.; Varga, Balazs V.; Teal, Carter J.; Morshead, Cindi M.; Nagy, Andras; Shoichet, Molly S.
Abstract: Ischemic stroke results in a loss of neurons for which there are no available clinical strategies to stimulate regeneration. While preclinical studies have demonstrated that functional recovery can be obtained by transplanting an exogenous source of neural progenitors into the brain, it remains unknown at which stage of neuronal maturity cells will provide the most benefit. We investigated the role of neuronal maturity on cell survival, differentiation, and long-term sensorimotor recovery in stroke-injured rats using a population of human cortically-specified neuroepithelial progenitor cells (cNEPs) delivered in a biocompatible, bioresorbable hyaluronan/methylcellulose hydrogel. We demonstrate that transplantation of immature cNEPs result in the greatest tissue and functional repair, relative to transplantation of more mature neurons. The transplantation process itself resulted in the least cell death and phenotypic changes in the immature cNEPs, and the greatest acute cell death in the mature cells. The latter negatively impacted host tissue and negated any potential positive effects associated with cell maturity and the hydrogel vehicle, which itself showed some functional and tissue benefit. Moreover, we show that more mature cell populations are drastically altered during the transplantation process itself. The phenotype of the cells before and after transplantation had an enormous impact on their survival and the consequent tissue and behavioral response, emphasizing the importance of characterizing injected cells in transplantation studies more broadly. Graphical abstract: Image 1